Secnidazol`s effectiveness for the bacterial vaginosis treatment - Olga F. Serova; Galina M. Shmeleva; Natalia V. Shutikova (IP Berlin A.V., 2023)
Background. Bacterial vaginosis is an infectious non-inflammatory syndrome with polymicrobial etiology associated with dysbiosis of the vaginal biotope. Aim. To assess the clinical efficacy and safety of Secnidox in treating bacterial vaginosis in women 2059 years. Materials and methods. The study included 30 patients (mean age 31.14.7 years) with bacterial vaginosis who received 2 g of secnidazole (Secnidox) as a single dose. All patients were followed up by an obstetrician-gynecologist at two visits. Results. Secnidazole provided sanitation of the vagina. Normalization of clinical symptoms and laboratory tests was reported. Conclusion. Secnidazole showed good therapeutic efficacy and normalization of the vaginal microflora.